Primal fear [videorecording (DVD)] - Shagan, Steve; Biderman, Ann; Gere, Richard, 1949-; Linney, Laura; Mahoney, John, 1940-2018; Woodard, Alfre, 1953-; McDormand, Frances; Norton, Edward (Widescreen DVD collection., 1998)
A Chicago altar boy is accused of murdering the archbishop and a publicity hungry local attorney decides to defend him.